Highest and Best Use Analysis : Case Study of Vacant Land In Denpasar - I Wayan Priyana Sudharma; Dian Ayu Rahmadani (Global Academia Publisher, 2020)
Denpasar City is the capital of Bali Province, in the last few years the property business has developed quite rapidly. Jl. Teuku Umar Barat is one of the main roads in the city of Denpasar. In this area there are also empty lands that have not been utilized so that they do not provide maximum economic benefits. So that in order to maximize the economic benefits that vacant land can provide, a Highest and Best Use (HBU) study is needed. The Goal of Highest and Best Use analysis is determining whether or not the property is being used for its most profitable permitted use. The results of the HBU analysis show that the alternative mixed-use building hotel covering an area of 3,645 m2 and a shophouse covering an area of 8,910 m2 results in an NPV value is IDR187,637,261,135 and the land value is IDR 120,932,881,135 or an increase of 39.11% from its initial value.